In Vitro Rumen Fermentation of Maize Hay and Bajra Straw Based Total Mixed Ration Containing Different Feed Additives - Patel, Sneh D; Garg, Deendayal; Savsani, Harish H; Chavda, Jignesh A; Sharma, Arun K; Kalam, Sanket M (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted to investigate the efficacy of different feed additives on rumen fermentation of total mixed ration. TMR was prepared by taking maize hay, bajra straw and concentrate in the ratio of 30:30:40, and additives monensin 30 mg/kg (T1), cellulase 0.5%, (10,00,000 IU/g) (T2), xylanase 0.5% (1,50,000 IU/g) (T3), chitosan 1% (T4), sodium bicarbonate 1% (T5), magnesium oxide 1% (T6), combination of sodium bicarbonate + magnesium oxide 0.5% each (T7) and combination of cellulose + xylanase 0.5% each (T8) were added as eight treatments. Rumen liquor was collected from two adult Surti goats 2 h of post-feeding. All post-fermentation parameters were measured after 24 h of incubation. pH was significantly (p